2013
DOI: 10.1371/journal.pone.0073589
|View full text |Cite
|
Sign up to set email alerts
|

miR-206 Represses Hypertrophy of Myogenic Cells but Not Muscle Fibers via Inhibition of HDAC4

Abstract: microRNAs regulate the development of myogenic progenitors, and the formation of skeletal muscle fibers. However, the role miRNAs play in controlling the growth and adaptation of post-mitotic musculature is less clear. Here, we show that inhibition of the established pro-myogenic regulator miR-206 can promote hypertrophy and increased protein synthesis in post-mitotic cells of the myogenic lineage. We have previously demonstrated that histone deacetylase 4 (HDAC4) is a target of miR-206 in the regulation of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…It is believed to be a muscle enriched miRNA and might play a role in cardiac hypertrophy. 40 Overexpression may reduce the effects of inflammatory cytokines. 41 These results point to plausible cardioprotective mechanisms for these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be a muscle enriched miRNA and might play a role in cardiac hypertrophy. 40 Overexpression may reduce the effects of inflammatory cytokines. 41 These results point to plausible cardioprotective mechanisms for these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs also play roles in muscle development in mammals. Previous studies reported that several miRNAs, such as miR-1, 47 miR-133, 31,45,49 and miR-206, 3,19,42 are musclespecific miRNAs because they are key regulators in muscle development in human, pigs, and rats. Others miRNAs may also contribute to muscle development.…”
Section: Introductionmentioning
confidence: 99%
“…In the reduced state, HDAC domain associates with the nuclear export signal (NES) and blocks its exposure to CRM1 exportin. After oxidation of Cys-667 and Cys-669, the HDAC domain dissociates from the NES, which is exposed to CRM1, inducing the nuclear export (46). Such mechanism has been described in lung carcinoma, where upon oxidation, HDAC4 was expulsed from the nucleus, leading to derepression of miR-206 (28).…”
Section: Discussionmentioning
confidence: 96%
“…HDAC4 is also a bona fide target of miR-206 (43) with miR-206 inhibiting expression of HDAC4 and augmenting histone acetylation (46). Moreover, miR-206 is not only a repressor of HDAC4 but also its downstream target.…”
Section: Discussionmentioning
confidence: 99%